Analysis of urban subway construction collapse disaster chain and research on chain breaking and disaster reduction - Ying Zhang; Yingying Gu; Ningning Lian; Lei Peng; Yu Hao; Wei Wang; Rumeng Tian (PLoS ONE, 2025)
In recent years, China ‘s major cities set off a climax of subway construction, but also brought an endless stream of safety accidents. In order to analyze the impact of the evolution process of urban subway construction collapse disaster on residents ‘ life and social economy, by collecting typical cases of subway construction collapse disaster, combined with disaster chain and complex network theory, the network model of subway construction collapse disaster chain is constructed, and the key node events and key propagation paths are analyzed. Based on this, targeted chain-breaking disaster reduction measures are proposed. The results show: the collapse disaster chain of urban subway construction can be divided into early, middle and late stages of disaster evolution. Through the destruction of collapse, underground pipeline rupture, road damage, affecting the lives of residents and building damage and other key nodes or cut off the collapse →  underground pipeline rupture, road damage →  traffic paralysis, collapse →  building damage, construction technology is not standardized →  collapse, construction equipment failure →  collapse and other key effects are significant. The relevant research results can provide a knowledge map for effectively coping with the collapse disaster chain of urban subway construction, identify key nodes and propagation paths, and establish strategies for emergency response and chain-breaking disaster reduction.